Kurdish Female Fighters the Western Depiction of YPJ Combatants in Rojava (Glocalism: Journal of Culture, Politics and Innovation, 2019)
As this paper is drafted, the YPJ continues to clash against Daesh’s patriarchal impositions. This paper considers three significant questions for its purpose; first, who are Kurdish female fighters and why did they choose to take up arms in an orga- nized militia? Second, how did the Western media portray the YPJ? Third, it consid- ers whether the Western representation of female soldiers is coherent or not with the subject. In conclusion, the essay will attempt to summarize in a nutshell the reality of the Kurdish female fighters. The aim of this essay is to identify a possible misrepresentation of the objective entailed in Rojava’s liberation struggle, since this could com- promise the real understanding of the subject, withholding from the audience the opportunity to learn about the plight of the Kurdish female fighters. The study of YPJ’s representation was pursued with the Analysis of Textual Data (ATD). However, the subject material for the socio-political analysis on the background of YPJ fighters was pursued through reference to books and interviews of Western reporters that were engaged in Rojava. Furthermore, a written interview was submitted to Meral Çiçek, of REPAK (Kurdish Women’s Relation Office). The results show an overall heterogeneous representation of the subject, as it is still not entirely exhaustive. The socio- political and ideological stand of YPJ combatants is often not addressed in a proper manner, therefore diminishing some aspects of their struggle. While Western fascination with Kurdish female fighters has slowed down, the YPJ battle is still ongoing. To that regard, the analysis in this paper ought to be considered as a starting point for further research.
Keywords: YPJ; Rojava; Kurdish female movement; gendered militarization; Western media